Loss of synaptic ribbons is an early cause in ROS-induced acquired sensorineural hearing loss - Shunkou Kurasawa; Hiroaki Mohri; Keiji Tabuchi; Takehiko Ueyama (Neurobiology of Disease, 2023)
Considerable evidence of reactive oxygen species (ROS) involvement in cochlear hair cell (HC) loss, leading to acquired sensorineural hearing loss (SNHL), were reported. Cochlear synaptopathy between HCs and spiral ganglion neurons has been gathering attention as a cochlear HC loss precursor not detectable by normal auditory evaluation. However, the molecular mechanisms linking ROS with HC loss, as well as the relationship between ROS and cochlear synaptopathy have not been elucidated. Here, we examined these linkages using NOX4-TG mice, which constitutively produce ROS without stimulation. mRNA levels of Piccolo 1, a major component of the synaptic ribbon (a specialized structure surrounded by synaptic vesicles in HCs), were decreased in postnatal day 6 NOX4-TG mice cochleae compared to those in WT mice; they were also decreased by noise exposure in 2-week-old WT cochleae. As noise exposure induces ROS production, this suggests that the synaptic ribbon is a target of ROS. The level of CtBP2, another synaptic ribbon component, was significantly lower in NOX4-TG cochleae of 1-month-old and 4-month-old mice compared to that in WT mice, although no significant differences were noted at 1.5- and 2-months. The decrease in CtBP2 plateaued in 4-month-old NOX4-TG, while it gradually decreased from 1 to 6 months in WT mice. Furthermore, CtBP2 level in 2-month-old NOX4-TG mice decreased significantly after exposure to cisplatin and noise compared to that in WT mice. These findings suggest that ROS lead to developmental delays and early degeneration of synaptic ribbons, which could be potential targets for novel therapeutics for ROS-induced SNHL.